2019
DOI: 10.1002/ana.25505
|View full text |Cite
|
Sign up to set email alerts
|

Residual descending motor pathways influence spasticity after spinal cord injury

Abstract: Objective: Spasticity is one of the most common symptoms manifested in humans with spinal cord injury (SCI). The neural mechanisms contributing to its development are not yet understood. Using neurophysiological and imaging techniques, we examined the influence of residual descending motor pathways on spasticity in humans with SCI. Methods: We measured spasticity in 33 individuals with motor complete SCI (determined by clinical examination) without preservation of voluntary motor output in the quadriceps fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 55 publications
7
51
0
Order By: Relevance
“…Participants with a MAS score of 1 and ϩ1 were grouped together as MAS 1. Recently, we observed no differences in outcomes related to spasticity between individuals with MAS score of 0 and 1 ( post hoc analysis not reported in the paper) (Sangari et al, 2019). The same result was observed here.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Participants with a MAS score of 1 and ϩ1 were grouped together as MAS 1. Recently, we observed no differences in outcomes related to spasticity between individuals with MAS score of 0 and 1 ( post hoc analysis not reported in the paper) (Sangari et al, 2019). The same result was observed here.…”
Section: Methodssupporting
confidence: 89%
“…medication to reduce spasticity are unable to modulate corticospinal responses, as is found in individuals that do take antispastic medication (Barry et al, 2013;Bunday et al, 2014), which is consistent with the view that corticospinal responses are affected when spasticity is present. This also agrees with recent results in humans with motor complete SCI showing that MEPs elicited by TMS were only present in spastic but not in nonspastic participants (Sangari et al, 2019). Second, we found that the magnitude of maximal voluntary output was decreased in spastic compared with non-spastic and control subjects.…”
Section: Corticospinal and Reticulospinal Contribution To Spasticity supporting
confidence: 93%
See 1 more Smart Citation
“…For instance, it has been demonstrated that in people with SCI amplitudes of MEPs are reduced, latencies are prolonged, and motor thresholds are increased compared to uninjured controls (Davey et al, 1998;Ellaway et al, 2007). Alterations in corticospinal function have been shown to relate to the functional recovery of limbs after SCI (Belci et al, 2004;Wirth et al, 2008;Sangari et al, 2019). Previous work on the trunk has shown that the MEP latencies in paraspinal muscles were prolonged in SCI patients with severe motor impairment compared with those with mild motor impairment (Ogura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted therapy of an intact reticulospinal tract in rats with severe spinal cord contusion has been shown to result in the reorganization of the cortico-reticulospinal circuit and improvement of motor function (Asboth et al, 2018). Stimulation therapies targeting specific descending motor pathways using time-dependent stimulation techniques have shown substantial recovery of motor function after injury in humans (Bunday et al, 2018;Sangari et al, 2019).…”
Section: Functional Significance For Recovery After Scimentioning
confidence: 99%